Synthesis and electrochemistry property of new crowded multi-ferrocenyl substituted benzene derivatives. (15th October 2016) - Wang, Ya-Qi; Sun, Qi; Han, Li-Min; Li, Hui; Gao, Yuan-Yuan; Yin, Qiang; Suo, Quan-Ling
Graphical Abstract: Five new sterically crowded multi-ferrocenyl and ferrocenylethynyl substituted benzene derivatives were synthesized by [2+2+2] cycloaddition reactions of 1, 4-bis(ferrocenyl)butadiyne with cobalt clusters Co2 (CO)6 (μ2 -η 2 -FcCCH) and Co2 (CO)6 (μ2 -η 2 -C9 H7 CCSiMe3 ). Their electrochemical properties were investigated by cyclic and square wave voltammetry, which were used to determine the molecular structure of one position isomer. Abstract: A series of new sterically crowded multi-ferrocenyl and ferrocenylethynyl substituted benzene derivatives, 1, 2, 4-triferrocenyl-3, 5-diferrocenylethynylbenzene (2 ), 1, 3, 5-triferrocenyl-2, 4-diferrocenylethynylbenzene (3 ), 1-indenyl-2-trimethylsilyl-4, 5-diferrocenyl-3, 6-diferrocenylethynylbenzene (4 ), 1-indenyl-2-trimethylsilyl-4, 6-diferrocenyl-3, 5-diferrocenylethynylbenzene (5 ), 1-indenyl-2-trimethylsilyl-3, 5-diferrocenyl-4, 6-diferrocenylethynylbenzene (6 ) were synthesized by [2+2+2] cycloaddition reactions of 1, 4-bis(ferrocenyl)butadiyne with cobalt clusters Co2 (CO)6 (μ2 -η 2 -FcCCH) and Co2 (CO)6 (μ2 -η 2 -C9 H7 CCSiMe3 ) (1 ) [where C9 H7  = indenyl, Fc = ferrocenyl, Me = methyl], and characterized by FT-IR, NMR, MS and elemental analysis. The crystal structures of compounds1, 3 –5 were determined by X-ray single crystal diffraction analysis for the first time. The electrochemical results of compounds2 –6 studied by cyclic voltammetry and square wave voltammetry indicate the wave splitting and the electronic interactions of2 –6 are related to the directly bonded ferrocenyl termini. Compounds4 –6 are three isomers, of which the molecular structures could be identified by their electrochemical properties and structural information.